PENGARUH STRATEGI PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA BEAT DI KABUPATEN LAMPUNG TENGAH (Studi pada Tunas Dwipa Matra Cabang Trimurjo) - Yoga Aditya Anggana Putra (Universitas Bandar Lampung (UBL), 2017)
In the modern era of increasing people’s needs, especially motorcycles. Honda motorcycles is a motorcycles of the Japanese manufacturer has worldwide because it is known for its fuel economy engine oil and obstinacy that created by Honda motorcycles, Honda motorcycles therefore always be excellent among motorcycle. The researchers took the title with a focus on brand Honda Beat motorcycles. This study aims to determine the effect of promotions on purchasing decisions Honda Beat motorcycle, to find out the effect of price on purchase decisions Honda Beat motorcycle, to determine the effect of promotion and price on purchase decisions Honda Beat motorcycle. This research was conducted in Lampung Tengah regency with respondents in the study as many as 80 respondents. This type of research used explanatory research or hypotheses. Data analysis technique, authors use regression technique with structural equation modeling as hypothesis testing. Variables that researchers use there are three, namely: promotion, pricing and purchasing decisions. The results obtained from this study showed that there is significant influence between promotion with purchasing decisions Honda Beat motorcycle. The existence of significant influence between prices and purchasing decisions Honda Beat motorcycle. The existence of significant influence of promotions and price with the purchasing decisions Honda Beat motorcycle. Keywords: Promotion, Pricing, Purchasing Decisions